O trabalho colaborativo no Atendimento Educacional Especializado (AEE) na perspectiva Histórico-Cultural - Pires, Michaelli Maria (2024)
Specialized Educational Assistance (AEE) is a service that can support, complement and/or supplement the schooling process in conjunction with the work carried out in the ordinary classroom. The principle of this service is to guarantee the full participation of the special education population in all educational stages and modalities. The research, focusing on ESA in the early years of elementary school, sought to understand the pedagogical practice carried out in ESA and its collaborative principle. To this end, we used bibliographical, documentary and field research procedures, with instruments such as a survey of current productions on the subject; legislative and guiding documents; interviews with teachers from the ESA, the common room and pedagogical coordination. It has the theoretical support of cultural-historical theory and the theory of study activity, as it is understood that these theories have a prospective view of the learning and development of people with disabilities, considering the various forms and ways of achieving this, in other words, a path of possibilities that considers the formation of human characteristics in the relationship between the biological and the social in a dialectical way, under the influence of historical-cultural conditions. The research allowed us to understand the organization and principles of the work developed in the ESA offered in the Multifunctional Resource Room (SRM), as well as to deepen our conceptual understanding of collaborative work and how essential this principle is to promoting learning that mobilizes the development of all students. We observed that in the school reality, the study activity and its constitution depend on cultural, historical and social factors and on the possibility of teachers in the network having access to training that contributes to the organization of teaching and learning processes. The research therefore met the criteria of the line Teacher training and teaching and learning processes because it sought to understand the demands of the teachers surveyed, as well as generalizing the data as a driver for new research and effective practices.